Thermal expansion in Prussian Blue analogs M3(Cr(CN)6)2.nH2O (M = Mn, Fe, Co, Ni) - Adak, Sourav; Daemen, Luke L.; Hartl, Monika; Pandey, Aman Kumar; Nakotte, Heinz (Solid state sciences, 2024)
Thermal expansion in Prussian Blue Analogs (PBAs) M3[Cr(CN)6]2.nH2O (M = Mn, Fe, Co, Ni; n = 10-16) was studied using powder X-ray diffraction (XRD) as a function of temperature in the range 123-298 K. Standard chemical precipitation was used to prepare the materials and they were characterized using standard characterization techniques XRD, X-ray fluorescence (XRF), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy. All materials were found to crystallize in the cubic structure with space group Fm3‾m. Strong compositional dependence of thermal expansion is found in this series of PBAs. While Mn3[Cr(CN)6]2.12H2O and Ni3[Cr(CN)6]2.16H2O show positive thermal expansion (PTE) behavior the other two PBAs, Fe3[Cr(CN)6]2.10H2O and Co3[Cr(CN)6]2.14H2O, show strong negative thermal expansion (NTE) behavior with as large coefficient of thermal expansion (CTE) as −19.7 x 10−6 K−1 (for M = Fe) in the temperature range 123-223 K. For the PBAs showing NTE, the magnitude of NTE coefficients can be correlated with the trends for M cation size and cell (or lattice) parameter.
Im Titel stehen alle Ziffern tiefgestellt, der Ausdruck "Cr(CN)6" steht in eckiger Klammer
Online verfügbar: 26. September 2024, Artikelversion: 01. Oktober 2024
Gesehen am 11.04.2025